(untitled) (Swiss Medical Weekly, 2019)
BACKGROUND Information on diagnoses made in emergency departments situated in rural sub-Saharan Africa is scarce. The aim was: to evaluate the frequency of different diagnoses made in a new emergency department to define relevant healthcare requirements; and to find out if in-hospital mortality rates would decrease after the implementation of the emergency department. METHODS In this observational study, we prospectively collated diagnoses of all patients presenting to the emergency department of the St Francis Referral Hospital in Ifakara, Tanzania during 1 year. In addition, we compared in-hospital mortality rates before and after the implementation of the emergency department. RESULTS From July 2016 through to June 2017, a total of 35,903 patients were included. The median age was 33.6 years (range 1 day to 100 years), 57% were female, 25% were children <5 years, 4% were pregnant and 9% were hospitalised. The most common diagnoses were respiratory tract infection (12.6%), urinary tract infection (11.4%), trauma (9.8%), undifferentiated febrile illness (5.4%), and malaria (5.2%). The most common clinical diagnoses per age group were: lower respiratory tract infection (16.1%) in children <5 years old; trauma (21.6%) in 5- to 17-year-olds; urinary tract infection (13.5%) in 18- to 50-year-olds; and hypertensive emergency (12.4%) in >50-year-olds. Respiratory tract infections peaked in April during the rainy season, whereas malaria peaked 3 months after the rainy season. In-hospital mortality rates did not decrease during the study period (5.6% in 2015 vs 7.6% in 2017). CONCLUSIONS The majority of diagnosed disorders were of infectious or traumatic origin. The majority of febrile illnesses were poorly defined because of the lack of diagnostic methods. Trauma systems and inexpensive accurate diagnostic methods for febrile illnesses are needed in rural sub-Saharan Africa.